SOME ISSUES OF PEDAGOGICAL IMAGE FORMATION IN FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
This article analyzes the pedagogical image and its features, various approaches to forming the image of a teacher, and describes effective methods. Also in the article, the author proposed rules for forming a pedagogical image.